Cambio de color arlequín en un neonato positivo a COVID-19: Reporte de caso - Pinel-Guzmán, Esther (2023)
Harlequin color change is a benign, idiopathic, self-limiting disorder characterized by the appearance of skin divided into two distinctly colored areas. Its etiology is unknown but thought to be caused by immaturity of hypothalamic regulation of peripheral vascular tone. COVID-19 infection in neonates is infrequent and rarely symptomatic, with only a few cases described in the literature. In isolation, both conditions have a low incidence. It is the first case reported in the world literature of harlequin color change in a newborn who tested positive for COVID-19. There isn’t a single publication that links harlequin color change to COVID-19.